Application of real options in decision-making in power markets [Aplicación de las opciones reales en la toma de decisiones en los mercados de electricidad] (2014)
Strategic investment decisions in power markets are subject to high risk and uncertainty, therefore Real Options appear to be an appropriate tool to assess the decision-making processes in such markets. This paper presents a literature review, analyzing and classifying Real Options applications in power markets on investments and operation decisions; energy policy and programs. A synthetic application model is presented using binomial models to introduce wind power instead of coal fired plants according coal prices volatility. Finally it is concluded that Real Options improves the decision-making processes better than traditional methods, as it better captures the uncertainties of this kind of market. © 2013 Universidad ICESI. Published by Elsevier Espanã, S.L.U. All rights reserved.